1996
DOI: 10.1111/j.1651-2227.1996.tb14168.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of brain lactate levels to predict outcome after perinatal asphyxia

Abstract: Perinatal asphyxia is an important cause of neurological disability, but early prediction of outcome can be difficult. We performed proton magnetic resonance spectroscopy (MRS) and global cerebral blood flow measurements by xenon-133 clearance in 16 infants with evidence of perinatal asphyxia. Cerebral blood flow was determined daily in the first 3 days after birth in seven cases. Proton MRS was performed in 11 infants within the first week (mean 3.7 days), the rest within the first month (mean 22.2 days), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 30 publications
3
28
1
Order By: Relevance
“…Elevated Lac levels have been shown until months after the hypoxiaischemia, probably due to an influx of Lac-producing macrophages in the damaged tissue or an altered redox state (36,38,39). Lac/NAA was significantly elevated in the group with abnormal outcome, as in previous reports (1,6,32,40,41). Only three neonates were examined during the first day of life, so most of the Lac found is probably due to secondary energy failure and influx of macrophages (42).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Elevated Lac levels have been shown until months after the hypoxiaischemia, probably due to an influx of Lac-producing macrophages in the damaged tissue or an altered redox state (36,38,39). Lac/NAA was significantly elevated in the group with abnormal outcome, as in previous reports (1,6,32,40,41). Only three neonates were examined during the first day of life, so most of the Lac found is probably due to secondary energy failure and influx of macrophages (42).…”
Section: Discussionsupporting
confidence: 50%
“…Using 1 H-MRS, decreases in NAA/Cho and NAA/Cr ratios were noted to predict poor neurodevelopment (1). An increased brain Lac, which, under normal circumstances, is present in only very small amounts in the neonatal brain and is hardly detectable by 1 H-MRS at term age, also predicts a poor outcome (3,6). These studies used TE of 272 or 136 ms (1,2,4,6).…”
mentioning
confidence: 99%
“…Previously, many studies have demonstrated decreased NAA/Cho ratios and elevated lactate/NAA ratios in neonates with HIE and a poor neurodevelopmental outcome [7,11,[23][24][25][26]. In the present study, NAA/Cho was not decreased in neonates with severe HIE.…”
Section: Discussionsupporting
confidence: 52%
“…Using 1 H-MRS, decreases in N-acetylaspartate (NAA)/choline (Cho) (NAA/Cho) ratios have been shown to predict poor neurodevelopment [7] An increase in brain lactate, which under normal circumstances is present in only very small amounts in the neonatal brain and is hardly detectable by 1 H-MRS at term age, has also been found to predict a poor outcome [8,11]. These studies used TEs of 272 or 136 ms [7][8][9]11]. With shorter TEs, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Elevated brain metabolite ratios, lactate/Nacetylaspartate (NAA) and lactate/choline, have been associated with poor neurodevelopmental status in neonates with hypoxic-ischemic encephalopathy. 1,10,12,13 The increase in brain lactate level is thought to be a result of anaerobic rather than oxidative energy metabolism during cellular hypoxia.…”
mentioning
confidence: 99%